Review of the genus Vertomannus Distant (Hemiptera: Heteroptera: Lygaeoidea: Rhyparochromidae: Ozophorini), with description of two new species - Li, Junlan; Bu, Wenjun (Zootaxa, 2015)
The ozophorine genus Vertomannus Distant, 1903 is reviewed in this paper. Ten species are recognized in the genus, including two new species, Vertomannus parvus sp. nov. and Vertomannus tibetanus sp. nov. The new species are described and illustrated. A key to all known members is included. Diagnosis of the genus, habitus photos, measurements, male genitalia illustrations, additional distributions are also presented.